The euro crisis and the responses to it: Missing the point? - Stefan Ederer (Intervention. European Journal of Economics and Economic Policies, 2012)
First paragraph: In the past two years the world economy experienced a patchy but relatively strong recovery. In the European Union, however, the upturn was markedly weaker than in the rest of the world. Buoyant exports to the fast-growing emerging economies led to a strong upswing in several countries of the EU (particularly Germany, but also Austria, Netherlands, Czech Republic, and Slovakia) and conveyed the impression that the financial and economic crisis of 2008/09 was over. It seemed that the crisis continued only in some peripheral countries with high government debt, mainly in Southern Europe.
Keywords: 330